Memperkasa geografi manusia di Malaysia: Isu dan cabaran - Amriah Buang, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2007)
This article articulates issues and challenges that are confronting the discipline of Geography, in particular, Human Geography, in Malaysia’s higher education. Preceded by a brief survey of the predicament in other countries in order to drive home the point that Malaysia is not unique in this matter, four main areas of empowerment issues and challenges are highlighted, namely: (i) Defending the unity of identity of Geography as a coherent and separate discipline in higher education; (ii) Ensuring the institutional survival of Geography in higher education; (iii) Ensuring the visibility of geographers’ role as public intellectuals; and (iv) Fostering the internationalization of Malaysia’s Human Geography. Outlining steps of empowerment in accordance with the issues and challenges identified constitutes the rest of the article